New insights into substrate preference and aryl ring migration mechanism for isoflavonoid biosynthesis - Moon Sajid; Parwinder Kaur (Current Research in Biotechnology, 2023)
Isoflavonoids are an essential source of bioactive compounds. Due to their enormous potential for human health, the demand for isoflavonoids is rising. Isoflavonoid synthase (IFS), a unique P450 monooxygenase, catalyzes the rate-limiting step in the biosynthesis of isoflavonoids. Here, IFS enzymes from five different plants are characterized for isoflavonoid biosynthesis in yeast. Although IFS generally prefers liquiritigenin as a substrate, this is the first time an IFS from Pueraria candollei has been characterised with a preference for naringenin. Co-expression of 2-hydroxyisoflavonoid dehydratase (HID) with IFS significantly improves isoflavonoids biosynthesis. However, a preference of IFS towards particular HID enzymes types was observed in this study. Additionally, the protein conformational basis of aryl ring migration mechanism has been explored for Onobrychis viciifolia IFS, P. candollei IFS, and CYP82D26 and compared with other P450 enzymes that accept the same substrates but do not produce isoflavonoids. Protein structure and docking analysis based on key amino acids, heme orientation, and IFS promiscuity has led us to suggest a new mechanism for aryl ring migration. Characterisation of IFS for efficiency, substrate preference, and understanding of aryl ring migration mechanism will help advance heterologous biosynthesis and protein engineering efforts.